Resettled Syrian refugees in Jordan: Survival or health promotion - Fatmeh Ahmad Alzoubi; Reem Ahmad Ali; Abduljawad Hasan Al‐Gharaibeh (Wiley, 2021)
Abstract Aim To assess the health promotion practices of Syrian refugees in the north of Jordan and to determine their correlation with some socio‐demographic variables. Design Cross‐sectional descriptive correlational. Methods Health‐Promotion Lifestyle Profile II (HPLP‐II) was used to measure health promotion practices of Syrian refugees. Data were collected from a convenient sample of 250 Syrian refugees who lived in the North of Jordan. Descriptive and inferential statistics were used to analyse data. Results The results showed that Syrian refugees in Jordan had low scores of total health promotion scale (mean = 2.28) with a cut score of 2.5, which indicated that they minimally adopted health promotion practices in general. The higher score was found on the interpersonal relation domain (mean = 2.89, SD 0.52). While the stress management domain (mean = 2.48, SD 0.43), spiritual growth domain (mean = 2.38, SD 0.39) and nutrition domain (mean = 2.34, SD 0.37) were lower than 2.5, the scores on responsibility and physical activity domains (mean = 2.20, SD 0.62), (mean = 1.35, SD 0.18) respectively, were the lowest. Women, married and unemployed, have more healthy behaviours than their counterparts.